INSTITUTIONAL CAPACITY OF LOCAL SELF-GOVERNMENT BODIES IN THE CONTEXT OF DESIGN THINKING AND MANAGERIAL CHANGES - Buryk, Zoriana (Public Management and Policy, 2026)
The study aims to examine and substantiate the specific features of the institutional capacity of local self-government bodies in fostering design thinking and implementing managerial transformations under contemporary conditions. In the process of writing the article, the author identified the features of the institutional capacity of local self-government bodies during the emergence of design thinking in improving managerial decisions. It was characterized that institutional capacity is understood as regulatory, legal, financial, resource and organizational support, and we also include human resources. No less significant, as highlighted, is the ability of local self-government bodies to adapt managerial decisions to modern crisis changes. The article details assessment methods for analyzing the institutional capacity of local self-government bodies in the process of forming design thinking, as well as analyzes socio-economic indicators for the period 2023-2025. The author tried to convey in the study that even with a shortage of time, human and financial resources, preference is still given to hierarchical and reactive management models. While the components of design thinking, we included empathic analysis of citizens' needs, participatory and preliminary testing of management decisions, motivate proactive decisions of residents. During the study, it was found that the introduction of the principles of design thinking in the activities of local self-government bodies implements the function of compensatory, contributes to transformation in the structure of informed management decision-making.